Modular evolution of the carnivoran pelvic girdle: a three-dimensional morphometric approach - Martín-Serra, Alberto; Figueirido-Castillo, Francisco Borja; Serrano-Lozano, Francisco; Palmqvist-Barrena, Carlos Paul (My University, 2015)
The pelvic girdle is a key skeletal structure within the appendicular skeleton in quadrupedal mammals. The pelvis anchors many important muscles and connects the hind limb to the axial skeleton. However, unlike other appendicular bones, each hemipelvis is composed of three different girdle bones: ilium, ischium and pubis. Here we investigate if the functional and developmental interactions among these bones accounts for the integration and modularity of the pelvis in mammalian carnivores. We use carnivorous mammals as a case study because our recent work has demonstrated that their appendicular skeleton is also integrated by functional reasons. A series of landmarks in 3D on one half of the pelvic girdle were digitized in a wide sample of living carnivorans. The landmarks were divided into four basic developmental units: illium, ischium, pubis and acetabulum. The latter was considered as a different unit because it interacts with the femoral head during development. Later, we tested different modularity hypotheses that consider all possible modules formed by the combination of these four developmental units. For each hypothesis, we calculated the RV coefficient, a proxy for morphological covariation. We compared each specific hypothesis with a distribution of RV coefficients resulting from randomly-defined modules to assess for statistical significance. One of the hypotheses with more statistical support separates the four original units as modules, which indicates a strong influence of development. Other supported hypotheses clearly point towards an association between the ischium and the pubis, with the illium and acetabulum more or less independent. However, these hypotheses cannot be unequivocally ascribed to functional interactions, because the ischium and the pubis also share some developmental processes. These results clearly indicate that the carnivoran pelvic girdle preserves a developmental modular structure with little modification attributable to functional adaptations, which agrees with previous studies that showed that the pelvis is conservative within each carnivoran family.
Martín-Serra, A., Figueirido, B., Serrano, F., Palmqvist, P. MODULAR EVOLUTION OF THE CARNIVORAN PELVIC GIRDLE: A THREE-DIMENSIONAL MORPHOMETRIC APPROACH. 75th meeting of Vertebrate Palaeontology. Dallas (Texas). Journal of Vertebrate Palaeontology Supplement (Program and Abstracts) P. 176
Keywords: Carnívoros - Morfología; Modularity; Pelvis; Carnivores; Morphometrics